2017
DOI: 10.1007/s10865-016-9821-z
|View full text |Cite
|
Sign up to set email alerts
|

A brief measure of reactance to health warnings

Abstract: Reactance to persuasive messages involves perceived threat to freedom, anger, and counterarguing that may undermine the impact of health warnings. To understand reactance’s effects, reliable and valid assessment is critical. We sought to develop and validate a brief Reactance to Health Warnings Scale (RHWS). Two independent samples of US adults completed the brief RHWS in studies that presented warnings on cigarette packs that smokers carried with them for 4 weeks (Study 1; n = 2149) or as digital images of ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 37 publications
1
48
0
Order By: Relevance
“…22 Parent trait reactance was assessed by using a brief scale that measures resistance that arises when a person feels their autonomy is threatened. 20 Intraclass correlation for the confidence model was 0.79, and intraclass correlation for the motivation model was 0.82. -, not applicable.…”
Section: Confidence By Hpv Vaccine Topicmentioning
confidence: 94%
See 1 more Smart Citation
“…22 Parent trait reactance was assessed by using a brief scale that measures resistance that arises when a person feels their autonomy is threatened. 20 Intraclass correlation for the confidence model was 0.79, and intraclass correlation for the motivation model was 0.82. -, not applicable.…”
Section: Confidence By Hpv Vaccine Topicmentioning
confidence: 94%
“…The survey assessed parents' attitudes toward vaccines in general (4 items; Cronbach's α = 0.84) and trait reactance (3 items; Cronbach's α = 0.61). 20,22 All items had 5-point responses that ranged from "strongly disagree" (coded as 1) to "strongly agree" (coded as 5). The survey company provided parent's demographic characteristics, including sex, age, race and ethnicity, and education.…”
Section: Sociodemographic Characteristicsmentioning
confidence: 99%
“…Details of the trial including protocols, survey development, and participant recruitment have been previously published (Brewer et al, 2016). Other papers using this dataset have explored mediators (Hall et al, In Press; Hall et al, 2017; Morgan et al, 2017) and trajectories (Parada, Hall, Boynton, & Brewer, 2017) of pictorial warnings’ impact, as well as attitudes toward the US Food and Drug Administration’s (FDA) regulation of tobacco products (Kowitt, Goldstein, Schmidt, Hall, & Brewer, 2017). In contrast, this paper explores public support of pictorial cigarette pack warnings.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, social interactions have been shown to be a mechanism of change in smoking-related campaigns (Jeong & Bae, 2017) and therefore could explain the impact of policy exposure on public support. Finally, building on reactance theory (Brehm, 1966; Brehm & Brehm, 1981) and research about reactance to pictorial warnings (Erceg-Hurn & Steed, 2011; Hall et al, In Press; Hall et al, 2017; LaVoie, Quick, Riles, & Lambert, 2015), it is plausible that reactance could weaken the impact of pictorial warning exposure on policy support.…”
Section: Introductionmentioning
confidence: 99%
“…When individuals perceive policies to be too restrictive, they may respond by ignoring such policies or opposing them. 21,22 Smokers, who likely place greater importance on tobacco than non-smokers, may therefore react more negatively to potential tobacco control policies. 21 Indeed, previous research has found that smokers are less supportive of tobacco control policies than non-smokers, 10,23,24 and while data are limited, smokers may react more negatively to tobacco control efforts, such as cigarette pack warnings.…”
Section: Introductionmentioning
confidence: 99%